Issuance of Crowd Permit for Hajatan Activities in Gresik Regency - Yudhis Wahyu Ramadhan; Rifqi Ridlo Phahlevy (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to determine how the process of applying for a crowd permit for celebration activities that use public facilities in the form of public roads and to find out whether the process of applying for a crowd permit for celebration activities in the Gresik Regency community is in accordance with PP 60 of 2017. This type of research uses normative research with a statute approach. The results of this study state that the process of applying for a crowd permit for activities in Gresik Regency is still in an oral form submitted to the local hamlet head which is not in accordance with PP 60 of 2017, and there is still a legal vacuum in Gresik Regency regarding the delegation of authority for what agency is authorized to issue a recommendation letter for a crowd permit in Gresik Regency.